Intellectual property protection and development: The case of sustainable sea transport in Pacific Island countries. (25th July 2017) - Forsyth, Miranda
Abstract: This paper is concerned with the impact of intellectual property laws on development in small island developing states. Much of the literature on intellectual property and development proceeds on the basis that there is only one model of each, namely the global model of intellectual property underpinned by the Agreement on Trade Related Aspects of Intellectual Property Rights and a neoliberal development framework. This paper argues, conversely, that there are multiple models of both. Exposing this plurality should enable a far more creative approach to intellectual property policy, particularly in countries whose levels of technological development and social structures are very different to those in the global North. This argument is explored through focusing on the example of sea transport.